Expression analysis of IFNAR1 and TYK2 transcripts in COVID-19 patients. (May 2022) - Akbari, Mohammadarian; Akhavan-Bahabadi, Mehdi; Shafigh, Navid; Taheriazam, Afshin; Hussen, Bashdar Mahmud; Sayad, Arezou; Fathi, Mohadeseh; Taheri, Mohammad; Ghafouri-Fard, Soudeh; Fathi, Mohammad
Abstract: As a member of JAK family of non-receptor tyrosine kinases, TYK2 has a crucial role in regulation of immune responses. This protein has a crucial role in constant expression of IFNAR1 on surface of cells and initiation of type I IFN signaling. In the current study, we measured expression of IFNAR1 and TYK2 levels in venous blood samples of COVID-19 patients and matched controls. TYK2 was significantly down-regulated in male patients compared with male controls (RME = 0.34, P value = 0.03). Though, levels of TYK2 were not different between female cases and female controls, or between ICU-admitted and non-ICU-admitted cases. Expression of IFNAR1 was not different either between COVID-19 cases and controls or between patients required ICU admission and non-ICU-admitted cases. However, none of these transcripts can properly diffrentiate COVID-19 cases from controls or separate patients based on disease severity. The current study proposes down-regulation of TYK2 as a molecular mechanism for incapacity of SARS-CoV-2 in induction of a competent IFN response.